1997
DOI: 10.1212/wnl.49.3.786
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal atrophy on MRI in normal aging and very mild Alzheimer's disease

Abstract: Magnetic resonance imaging(MRI) based volumetric measurements of medial temporal lobe (MTL) structures can discriminate between normal elderly controls and patients with Alzheimer's disease (AD) of moderate to advanced severity. In terms of clinical utility, however, a more important issue concerns the ability of the technique to differentiate between normal elderly controls and AD patients with the very mildest form of the disease. We performed MRI-based volume measurements of the hippocampus, parahippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
644
5
9

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 979 publications
(700 citation statements)
references
References 71 publications
(56 reference statements)
42
644
5
9
Order By: Relevance
“…Volumes of hippocampus and parahippocampal gyrus were found to decline significantly with age. Several authors have reported similar age-related volume decreases in these regions [8,9,12,18,26,31]. However, other authors have failed to find such a decline in medial temporal lobe volumes [24,31,37].…”
Section: Normal Brain Agingmentioning
confidence: 91%
“…Volumes of hippocampus and parahippocampal gyrus were found to decline significantly with age. Several authors have reported similar age-related volume decreases in these regions [8,9,12,18,26,31]. However, other authors have failed to find such a decline in medial temporal lobe volumes [24,31,37].…”
Section: Normal Brain Agingmentioning
confidence: 91%
“…In addition, subjects in this treatment trial were drawn from the recruitment base for the ADCS -dementia and memory disorders referral centers. Conversely, the majority of subjects in Mayo Clinic MRI studies are drawn from a community sample (Petersen et al, 1990;Jack et al, 1997).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Four different brain atrophy brain measures were assessed; the hippocampus, entorhinal cortex (ERC), whole brain, and ventricular volume. Each of these MRI measurements has figured prominently in anatomic MRI based studies of MCI, AD, and normal aging (Jack et al, 1992;Fox et al, 1996;Jack et al, 1997;Fox et al, 1999;Killiany 2000;Dickerson et al, 2001;Killiany et al, 2002;Du et al, 2003). A primary objective of this analysis was to test the hypothesis that vitamin E or donepezil slowed the rate of brain atrophy relative to placebo in subjects with amnestic MCI (Petersen 1995;Petersen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo magnetic resonance (MR) imaging studies have reported substantial volume loss in the hippocampus in subjects with very mild or mild dementia of the Alzheimer type (DAT) (Dickerson et al, 2001;Du et al, 2001;Fox et al, 1996;Jack et al, 1997;Killiany et al, 2002). However, structural deformation of the substructures of the hippocampus in early DAT has not been adequately examined.…”
Section: Introductionmentioning
confidence: 99%